Women in Mozambique: Gender Struggle and Gender Politics - Arnfred, Signe (Review of African Political Economy, 1988)
The liberation of women is a fundamental necessity for the revolution, a guarantee of its continuity and a condition for its success (Machel, 1973). In his opening address to the first conference of the Mozambique Women's Organisation (OMM) in 1973, Samora Machel, President of Frelimo, affirmed that women's emancipation was an integral aspect of revolutionary struggle. In 1973 Frelimo was still a liberation front engaged in armed struggle against colonial rule. The northern part of Mozambique was a battle ground and the first OMM conference had to be held in the Frelimo camp at Tunduru in southern Tanzania. In the OMM's present national. secretariat in Maputo, a photograph of the participants of this first conference can be seen. Peasant women and women guerilla's are lined up outside the meeting hut, amongst them Samora Machel in battledress. The non-hierarchical atmosphere depicted in this photograph is in marked contrast to the more formal arrangements on similar later occasions. The participation of women in the war was massive. In 1967, at the request of women themselves, a women's detachment of the guerilla army - Destacamento Feminino - had been formed. Part of its task was to inform and mobilise the peasant population. To support this work, a broader non-military organisation of women was needed. This was the origin of the foundation of the OMM in 1973.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; gender / género

The dynamics of health policies in Mozambique 1975–85 - Walt, Gill; Cliff, Julie (Health Policy and Planning, 1986)
In 1985 Mozambique commemorated its tenth year of independence against a background of a continuing need to defend the country, not only against the actions of the externally-backed Mozambique National Resistance (MNR), but also against drought, acute food shortages and a world economic recession. These external factors have significant implications for the implementation of Mozambique's health policy. The MNR has chosen as deliberate targets for attack: health posts, health centres, rural hospitals, even health workers. Ambushes and the mining of roads and electricity pylons have interrupted the supply and storage of drugs, the maintenance of immunization programmes and the support and supervision of health personnel. Food and water shortages have put lives at risk. These external factors are exacerbating some of the urban and rural class struggles which have become more apparent in the last few years and which, taken together, challenge the direction of health policy. This paper first sets the geographical context of Mozambique's independence. It goes on to explore how health policy was forged through theory and practice over a ten-year period of armed struggle. A brief discussion of health in the colonial state and some of the constraints faced in the first years of independence follows. Finally an attempt is made to assess the effects of both internal struggles and external factors on health policy ten years after independence.
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; health / saúde